Structural Planning of 6- Storey Hotel Building in Subang District - Nazarudin, Jabbaarru; Rizkyansyah, Zahran; Nurokhim, Sofyan; Sumarman , Sumarman (Green Publisher Indonesia, 2025)
The structural planning of multi-story buildings is a crucial aspect of the construction process, as it determines the extent to which a building can withstand loads and function safely throughout its service life. A well-designed structure will be resilient against various types of loads, including static loads such as the self-weight of the structure, as well as dynamic loads such as occupant activities, wind forces, and seismic forces. Therefore, structural planning must be carried out comprehensively and in accordance with applicable standards and regulations to ensure that the building possesses adequate strength, stability, and safety under various loading conditions. This study focuses on the structural planning and analysis of a six-story hotel building located in Subang Regency, West Java. In this research, local soil conditions and several national standards such as SNI 2847:2019, SNI 1727:2020, and SNI 1726:2019 are carefully considered. Structural analysis is carried out using ETABS version 22.6.0 to model and evaluate how the columns, beams, floors, and foundations are able to withstand all types of loads. The results of this study are expected to serve as a reference for designing similar building structures and to contribute to improving the quality of multi-story building planning in Indonesia.